Eliminating Intergenerational and Intercultural Communication Problems in Tourism and Hospitality Enterprises - Ineta Luka (Acta Universitatis Sapientiae: Philologica, 2023)
Tourism and hospitality is a versatile and multicultural industry that comprises collaboration between members of different generations and cultures in creating and selling a tourism product. Business communication, including tourism and hospitality, does not refer only to business etiquette but is strongly rooted in culture, which influences people’s interaction and way of speaking. Hence, intergenerational and intercultural communication problems are inevitable. The current research presents the main findings of an exploratory research conducted in tourism and hospitality enterprises in Latvia, Lithuania, and Sweden in the period of 2020–2023. To discover intergenerational and intercultural communication differences leading to communication problems, semi-structured expert interviews with top-level management representatives in twelve tourism and hospitality enterprises were conducted. The paper analyses intergenerational and intercultural communication problems in tourism and hospitality enterprises, in particular those concerning the use of different languages and ways of communication to suggest means of eliminating the existing problems. The research findings confirm that differences between generations had an impact on the communication process. However, the cultural background and languages influenced people’s behaviour even more, and a great majority of conflicts arose because of difference in cultures, not generations. Suggestions for staff training to develop their intercultural communication skills taking into account generational differences have been proposed.